2009
DOI: 10.1007/s11207-009-9445-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Spacecraft Observations: Stream Interactions and Associated Structures

Abstract: The stream interaction region (SIR), formed when a fast stream overtakes a preceding slow stream, is the predominant large-scale solar wind structure at this early phase of the STEREO mission. Using multi-spacecraft observations from STEREO A and B, ACE, Wind, and Ulysses in 2007, we analyze three stream interaction events in depth in May, August, and November of 2007, respectively, when the spacecraft had quite different spatial separations. We attempt to determine the causes of the differences in the SIR pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…At 1 AU, Jian et al (2006) have found that only 24% of SIRs have shocks. These shocks are still in a phase of building up at 1 AU, and the shocks are small and transient structures, as observed with multi spacecraft (Jian et al 2009). The sources of fast streams are typically large and stable coronal holes.…”
Section: Introductionmentioning
confidence: 63%
“…At 1 AU, Jian et al (2006) have found that only 24% of SIRs have shocks. These shocks are still in a phase of building up at 1 AU, and the shocks are small and transient structures, as observed with multi spacecraft (Jian et al 2009). The sources of fast streams are typically large and stable coronal holes.…”
Section: Introductionmentioning
confidence: 63%
“…1. In May 2007, the three spacecraft were very close, but the shocks driven by the same SIR were missed by one or two spacecraft, suggesting SIRdriven shocks were still in development at 1 AU and they were small or transient structures [e.g., 16,17]. In April -May 2008, when L1 and one STEREO spacecraft were separated by ~25 o in longitude, we started to see the absence of one SIR at one spacecraft.…”
Section: Survey Of Large-scale Solar Wind Structuresmentioning
confidence: 96%
“…Nevertheless, the PFSS model has proven very successful in identifying the open-field regions at the Sun and the largescale heliospheric structures such as magnetic sectors (e.g., Neugebauer et al 1998Neugebauer et al , 2002Wang & Sheeley 2006;Jian et al 2009;Lee et al 2009). More stringent tests of the PFSS model have come from mapping studies of impulsive SEP events (Nitta et al 2006;Nitta & DeRosa 2008;Rust et al 2008;MacNeice et al 2011).…”
Section: Sep Intervals and Imf Source Region Characterizationmentioning
confidence: 99%